Analisis Faktor Internal, Eksternal Dan Pembelajaran Kewirausahaan Yang Mempengaruhi Minat Mahasiswa Dalam Berwirausaha Studi Kasus Mahasiswa Universitas Islam Malang - Ihsan, Dedi Fatihul; Basalamah, Muhammad Ridwan; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aim is to analyze internal factors, external factors and entrepreneurial learning that influence student interest in entrepreneurship. Based on the results of the study it is known that internal factors have a positive effect on student interest in entrepreneurship. external factors have a positive effect on student interest in entrepreneurship. entrepreneurship learning factors have a positive effect on student interest in entrepreneurship. internal, external and entrepreneurial learning factors have a positive effect together on student interest in entrepreneurship. Keywords: Internal Factors, External Factors And Entrepreneurial Learning, Student Interest In Entrepreneurship